Pengaruh Pemeriksaan Pajak, Penagihan Aktif, dan Penerapan Sanksi Pajak Terhadap Intensifikasi Pajak Daerah Di Kota Bukittinggi - Melisa Melisa; Adriansyah Adriansyah (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This research aims to examine and analyze the effect of Tax Audits, Active Tax Collection, and the Implementation of Tax Sanctions on Local Tax Intensification in Bukittinggi City. This type of research is quantitative with an explanatory approach. The sampling method employed was a saturated sampling technique, involving all 70 respondents who served as officers responsible for tax audits, active tax collection, and the enforcement of regional tax sanctions in Bukittinggi City. Data collection was carried out through the direct distribution of questionnaires, and the data analysis technique was processed using SmartPLS 4 software through the evaluation of the measurement model (outer model) and the structural model (inner model). The results show that Tax Audits do not have a positive and significant effect on Local Tax Intensification, indicating a low audit coverage ratio due to the limited number of functional tax auditors. Conversely, Active Tax Collection is proven to have a positive and significant effect on Local Tax Intensification through disciplined and timely delivery of Warning Letters and Distress Warrants. Furthermore, the Implementation of Tax Sanctions was found to be the most dominant and superior predictor with the largest effect size in creating a preventive deterrent effect for taxpayers. Simultaneously, the Coefficient of Determination (R2) indicates that the combination of these three independent variables can explain the variance of Local Tax Intensification by 79.0%, while the remaining 21.0% is explained by other variables outside this research model.